Clinical Applications of Artificial Intelligence in positron emission tomography of Lung Cancer - Zukotynski, Katherine; Gaudet, Vincent C.; Uribe, Carlos F.; Chiam, Katarina; Benard, Francois; Gerbaudo, Victor (Elsevier, 2022)
The ability of a computer to perform tasks normally requiring human intelligence or artificial intelligence (AI) is not new. However, until recently, practical applications in medical imaging were limited, especially in the clinic. With advances in theory, microelectronic circuits and computer architecture as well as our ability to acquire and access large amounts of data, AI is becoming increasingly ubiquitous in medical imaging. Of particular interest to our community, radiomics tries to identify imaging features of specific pathology that can represent for example the texture or shape of a region in the image. This is done based on a review of mathematical patterns and pattern combinations. The difficulty is often finding sufficient data to span the spectrum of disease heterogeneity since many features change with pathology as well as over time and, among other issues, data acquisition is expensive. Although we are currently in the early days of the practical application of AI to medical imaging, research is ongoing to integrate imaging, molecular pathobiology, genetic make-up and clinical manifestations to classify patients into subgroups for the purpose of precision medicine, or in other words, predicting a priori treatment response and outcome. Lung cancer is a functionally and morphologically heterogeneous disease. Positron emission tomography (PET) is an imaging technique with an important role in the precision medicine of lung cancer patients that helps predict early response to therapy and guides the selection of appropriate treatment. Although still in its infancy, early results suggest the use of AI in PET of lung cancer has promise for the detection, segmentation and characterization of disease as well as for outcome prediction.
The final publication is available at Elsevier via https://doi.org/10.1016/j.cpet.2021.09.001. © 2022. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: lung cancer; Positron Emission Tomography; pulmonary nodule; cancer diagnosis; targeted therapy; artificial intelligence